1996
DOI: 10.1093/ndt/11.supp5.66
|View full text |Cite
|
Sign up to set email alerts
|

Localization of glycated proteins in the glomeruli of patients with diabetic nephropathy

Abstract: Glycation of proteins is regarded as one of the major causes of the development and progression of diabetic nephropathy. Based on the numerous reports on experimental models and on our own newly developed techniques, we planned to localize Amadori products and advanced glycation end-products (AGEs), as well as the mRNA expression of cytokines, enzymes and their inhibitors, which are responsible for the expansion of the mesangial areas of the glomeruli. Ten patients with diabetic nephropathy were examined. Pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
18
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 11 publications
2
18
0
Order By: Relevance
“…Chronic hyperglycemia results in the accumulation of advanced glycation end products (AGEs) in the body, which further increase the risk for vascular complications in patients with DM (31). A previous study demonstrated that AGEs are always present in diabetic individuals with kidney dysfunction, leading to the overproduction of ROS (32).…”
Section: Discussionmentioning
confidence: 99%
“…Chronic hyperglycemia results in the accumulation of advanced glycation end products (AGEs) in the body, which further increase the risk for vascular complications in patients with DM (31). A previous study demonstrated that AGEs are always present in diabetic individuals with kidney dysfunction, leading to the overproduction of ROS (32).…”
Section: Discussionmentioning
confidence: 99%
“…Administration of anti-glycated albumin antibody in animal models reduces plasma levels of glycated albumin, reduces AER, and reverses glomerular pathology (22). Human studies have been conflicting, perhaps in part because of small numbers and confounding by other risk factors, but one of the largest previous studies clearly indicated that Amadori albumin levels were elevated in individuals with nephropathy compared with individuals without nephropathy (15,(23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
“…8 -11 A recent clinical study has clearly shown an association between Amadori albumin and diabetic vascular complications. [12][13][14] AGEs exert their effects on cells by interacting with specific cellular receptors, the best characterized of which is the receptor for AGE (RAGE). 15,16 It has been demonstrated that AGE-RAGE interaction-mediated induction of cellular oxidant stress triggers a cascade of intracellular signals involving p21 ras and mitogen-activated protein kinase (MAPK), culminating in transcription factor activation.…”
mentioning
confidence: 99%